Military music in Costa Rica during the first half of the 20th century: distribution of knowledge, aesthetic values and patriotism - Araya Quesada, Mauricio (2018)
The importance of the Alajuela Military Band logbooks, and the information contained therein, has been discussed in two published articles. The first is an introduction, with preliminary results, and the second, presents a historical frame of reference and statistical results taken from the repertoire performed. This third article will further discuss just what a Costa Rican "military band" is and its role in the dissemination of musical knowledge and aesthetic values. The article will also include information about different personalities associated to these bands. In addition, an analysis of data obtained from documents used as illustrations will give us a better understanding of music in Costa Rica, between 1938 and 1946, in terms of Military Bands and the extent of their contact with the population.